2010
DOI: 10.1007/s00383-010-2648-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the most common complication after one-stage transanal pull-through in infants with Hirschsprung’s disease?

Abstract: TAPT has many advantages, low complications and the results are excellent. It seems the most common complication is anastomotic stricture that responds well to prophylactic bouginage. We recommend prophylactic anal bouginage with Hegar probe at 2 weeks after operation. Long-term follow-up is needed to evaluate the outcomes of our operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Rouzrokh et al observed in their series that after starting prophylactic anal dilatations, anastomotic strictures did not occur 10 ; this however was not the aim of their study and a literature search on the subject did not yield any studies that aimed to answer the question: "do dilatations prevent strictures?" It is possible that because anal dilatations are successful in managing established strictures, [5][6][7][8][9][10]24,26 some pediatric surgeons have interpreted this to mean that dilatations should be just as effective in preventing strictures. Unfortunately, strictures can occur early or late, 6,27 which may be after the period of recommended dilatation program has ended and occasionally are only amenable to stricturoplasty or redo pull-through.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rouzrokh et al observed in their series that after starting prophylactic anal dilatations, anastomotic strictures did not occur 10 ; this however was not the aim of their study and a literature search on the subject did not yield any studies that aimed to answer the question: "do dilatations prevent strictures?" It is possible that because anal dilatations are successful in managing established strictures, [5][6][7][8][9][10]24,26 some pediatric surgeons have interpreted this to mean that dilatations should be just as effective in preventing strictures. Unfortunately, strictures can occur early or late, 6,27 which may be after the period of recommended dilatation program has ended and occasionally are only amenable to stricturoplasty or redo pull-through.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recommended duration of the dilatation program is not clear; some authors have recommended from 3 to 8 weeks post pull-through 7 whereas others recommend up to 6 months post pullthrough. 10 It is generally accepted that the dilatations should commence at least 2 to 3 weeks post pull-through for fear of disrupting the anastomosis. 7,10,24 For ARM, Levitt and Peña have stated that the unused narrow rectum post PSARP require twice daily dilatations from 2 weeks to approximately 3 months postoperatively or till the desired size of the neoanus is reached before the child's colostomy is closed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then we did not have anastomo c stricture. Rou ne anastomo c dilata on has been recommended by several other authors 7,18,20 . Enteral feeding 21 was done and there were a few episodes of vomi ng without abdominal disten on in six subjects which improved with me without medica on.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic complications, particularly stricture or leak, are uncommon, occurring with an incidence of 4% to 22% in reported series [4][5][6][7][8][9][10]. Because these complications can have devastating consequences and can impair the long-term functional quality of life for these children, most surgeons traditionally required diligent daily anal dilatation programs to avoid anastomotic stricture.…”
mentioning
confidence: 99%